Survival Analysis of Surgical Tracheotomy in Pediatric Patients With Chronic Diseases in a Tertiary Health Center - Osman Erdoğan; Hatice Feray Arı; Betül Aktaş Kipoğlu; Sefa İncaz; Ahmet Yükkaldıran (The Turkish Journal of Ear Nose and Throat)
Objective: To investigate the effect of age group (infants and non-infants) and demographics on survival in pediatrics with tracheotomy.Materials and Methods: Sex, age at the time of the tracheotomy, nationality, parental consanguinity, primary disease, date of discharge from the intensive care unit, and date of death were obtained from the medical records. The study population was categorized by nationality, parental consanguinity, and age group for survival analysis.Results: The study included 140 pediatric patients who underwent a tracheotomy. The median age of the patients at the time of the tracheotomy was 1.23 years. The median follow-up after tracheotomy was 5.4 months. Consanguinity was present in 70.4% of the parents. Primary diseases were grouped as neurologic (37.1%), neuromuscular (29.3%), metabolic (12.1%), cardiopulmonary (8.6%), traumatic (6.4%), and syndromic (6.4%). Neuromuscular diseases were more common in infants, while neurologic and metabolic diseases were more common in non-infants. Eighteen patients were weaned and four patients were decannulated. The overall mortality rate was 70%. The median overall survival was 214 days. Infants (147 days) had a shorter survival than non-infants (286 days). Parental consanguinity and nationality did not affect survival.Conclusion: In this study, among pediatric patients, infants are associated with a poor prognosis in survival. Neurologic and neuromuscular diseases may be thought to increase mortality among primary diseases. According to our study, it can be suggested that infants who cannot be decannulated due to neuromuscular diseases and are discharged with a tracheostomy are the group that should receive most attention regarding mortality among pediatrics with a tracheostomy.